PENGARUH NILAI PELANGGAN TERHADAP KEPUASAN SERTA DAMPAKNYA TERHADAP LOYALITAS MENGGUNAKAN SMARTPHONE SAMSUNG GALAXY SERIES DI KOTA PALU - Wijanarko, Koko Sigit (Katalogis, 2014)
The objectives of this researchare: (1) to know and analyze the effectscustomer value on customer satisfaction to use smartphone Samsung Galaxy series in Palu City, (2) to know and analyze the effectscustomer value on customer loyalty, (3) to know and analyze the effectscustomer satisfaction on customer loyalty. This is a descriptive causal research to investigate interrelationships among customer value, satisfaction and loyalty involving 220 respondents that have been selected using purpose sampling technique. Based on the results of Structural Equation Modeling, it shows that: (1) customer value performs significant effect on customer satisfaction; (2) customer value does not perform significant effect oncustomer loyalty; (3) customer satisfaction performs significant effect on customer loyaltyto use smartphone Samsung Galaxy series in Palu City.